Shedding Light on Electricity Utilities in the Middle East and North Africa : Insights from a Performance Diagnostic - Camos, Daniel (World Bank, Washington, DC, 2018)
The electricity sector in the Middle East and North Africa (MENA) is in the grip of an apparent paradox. Although the region is home to the world's largest oil and gas reserves and has been able to maintain electricity access rates of close to 100 percent in most of its economies, it may not be able to cater to the future electricity needs of its fast-growing population and their business activities. Primary energy demand is expected to rise at an annual rate of 1.9 percent through 2035, requiring a significant increase in generating capacity. Investments have not been rising fast enough to meet that requirement.